Design of Information System for Pajjaiang Makassar Clinic Based on Web and Mobile - Alwali, Muhammad; Bastian, Alvian; Asriyadi, Asriyadi (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
The role of information technology is currently developed according to the current rapid development of the times. The most developed types of information technology are web-based and mobile devices. Web-based and mobile devices are used to facilitate daily activities along with technological advances. One of the important things for everyday life by utilizing technological advances is in the field of health services, especially services at health clinics. In this regard, a web-based and mobile information system was designed at the Pajjaiang Makassar clinic to facilitate service. Making this system uses the waterfall method which is often used in the development of information systems or software. This system consists of 4 actors, namely patients, admins, doctors, and pharmacists. Patients are connected to the mobile application, while admins, doctors, and pharmacists are connected on the web side. The patient registers for the examination, the admin manages the patient's data, the doctor conducts the examination, and the pharmacist manages the available drugs. Everything is interconnected using mysql database as the database and Application Programming Interface (API) to connect it. With this web-based and mobile information system is a form of digitalization process in the field of health services.